Development of CTL-Based Teaching Material Supplements in Biological Literacy Training - Dinda Fuji Islamiyanti; Lisdiana Lisdiana; Ari Yuniastuti (Universitas Negeri Semarang, 2023)
This study aims to develop supplemental CTL-based respiratory system teaching materials to train students' biological literacy skills. The quality of teaching material supplements is measured by the criteria of the characteristics of teaching material supplements, validity, readability and effectiveness of teaching material supplements when used in the learning process. The characteristics of teaching material supplements consist of 7 activities, namely Constructivism, Inquiry, Questioning, Learning community, Reflection, Authentic assessment. The validation of teaching material supplements was assessed by material experts and media experts. The results showed that the percentage of validity of teaching material supplements by material experts was 88.1% with very valid criteria and the mean validity by media experts was 96% with very valid criteria. The legibility of teaching material supplements was analyzed based on the readability questionnaire data for teachers and students after the trial was carried out at SMA Negeri 7 Cirebon City. The results of the teacher readability questionnaire were 87.7% very good criteria and 85.5% very good criteria for student readability. The effectiveness of teaching material supplements in training biological literacy skills was tested using the N-gain test obtained from the results of the pretest and posttest questions based on biological literacy. The mean value of the pretest is 48.15 and the posttest is 77.04. Biological literacy N-test gain with an average of 0.56 in the medium category. Based on the results obtained, it can be concluded that the developed teaching material supplements meet the criteria of characteristics, validity, readability and effectiveness and can train biological literacy skills.